Code Mixing and Switching Used in Breakout Music Program of Net TV - Lubis, Syahrul Efendi; Hendrawan, Dicky (Sinkron : jurnal dan penelitian teknik informatika, 2022)
Bilingual and multilingual people present language variety called Code – Mixing and Code – Switching. The purpose of this study is to find the kinds of code mixing and code switching that used by the hosts in Breakout a music program in Net TV and to conclude the factor that influence the hosts mix and switch their utterances. This study was done by using description/qualitative method. This study used three of selected episodes, each utterances in each episode changed into the scripts, and the scripts made into the table form. As the result of this study, in generally, the hosts used two kinds of Code Mixing, they are Intra sentential code mixing and extra sentential code mixing, and five kinds of Code Switching on their utterances (Situational, Metaphorical, Tag Code switching, Inter-sentential switching, and Intra-sentential switching). The hosts mix and switch their utterances influenced by the setting and scene, participants, ends, key, norm of interaction as described by Dell Hymes, and also found the other factors, they are background of language, topic and the limited Indonesian vocabularies which can be hazy if it puts in Indonesian.